NONLINEAR OPTICAL (NLO) MATERIALS: BIS(2-METHYL-4-NITROANILINIUM) HEXACHLORO-TIN(IV) MONOHYDRATE.SINGLE CRYSTAL X-RAY STRUCTURE ANALYSIS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
2-Methyl-4-nitroaniline (2m4na) and Tin(IV) chloride formed a nonlinear optical material. The molecula obtained nonlinear optical material (NLO)=(2m4na)2SnCl6·H2O-bis(2-Methyl-4-nitroanilinium) hexachloro-Tin (IV) monohydrate. In all the crystal structures presented, cations and anions are arranged alternatively to form chain and ring hydrogen-bonding patterns consisting of weak unconventional N−H•••Cl hydrogen bonds. The compound was first analyzed using single-crystal X-ray diffraction to determine its crystal structure. Subsequently, FTIR (Fourier-transform infrared spectroscopy) and UV-visible absorption spectroscopy studies were conducted to provide insights into the compound's chemical composition and electronic transitions.